Using vermicompost to reduce synthetic fertilizers in jalapeño pepper cultivation - Ayala-Tafoya, Felipe; Valdez-Islas, José Carlos; Rosales-Avitia, José Vladimir; Parra-Delgado, Juan Martín; Valenzuela-López, Marino; Yáñez-Juárez, Moisés Gilberto (Ecosistemas y Recursos Agropecuarios, 2025)
In contemporary agriculture, the emerging paradigm is to reduce or eliminate the use of synthetic fertilizers that adversely impact the environment. The use of composts constitutes a strategy to improve the efficiency of nutrition with reduced amounts of synthetic fertilizers. The objective of the research was to determine the capacity of vermicompost to reduce synthetic fertilization used in jalapeño pepper cultivation. A randomized block design with six treatments and six repetitions was used. The variables evaluated were plant height, stem diameter, leaf greenness index, leaf area index, dry biomass production per plant and fruit yield. The treatments that combined the application of 10 t ha-1 of vermicompost with 25 (T4), 50 (T3) and 75% of synthetic fertilizers (T2) induced effects on plant height, stem diameter, leaf greenness and leaf area index, like those obtained with the control treatment, with 100% synthetic fertilization (T1). However, the average effect of T2, T3 and T4 was to increase the dry weight per plant by 113.6%, the number of fruits per plant by 72.1%, the total yield by 100.6% and the yield of large-sized fruits by 21.3%, compared to the effect of the control treatment (T1). The application of 10 t ha-1 of vermicompost to the soil enables the reduction of synthetic fertilizers, from 25 to 75%, in jalapeño pepper grown under shade house conditions.
Keywords: Capsicum annuum L.; fruit yield; plant growth; synthetic fertilization; vermicompost